Influence of Spring Season Crop Residue on Productivity of Rice-Wheat Cropping System - Devkota, KP; Yadav, DN; Chaudhary, NK; Dangol, DR; Basnet, KB (Journal of the Institute of Agriculture and Animal Science, 2006)
A field experiment was conducted to determine the effect of cultivation and plant residue incorporation of blackgram [Vigna mungo (L.) Hepper], mungbean [Vigna radiata (L.) Wilczek], cowpea (Vigna sinensis L.), maize (Zea mays L.) and maize+blackgram on response of rice to two levels (0 and 90 kg ha-1) of nitrogen and their residual effects on nitrogen management of subsequent wheat crop. The experiment was carried out in Randomized Complete Block design in spring, Split Plot design in rainy, and Split-Split plot design in winter seasons of 2000 at Institute of Agriculture and Animal Science (IAAS), Rampur, Chitwan, Nepal. Results showed that cultivation and incorporation of different spring season crop’s (legume and cereal) residue into the soil did not significantly affect rice yield. Such trend was also observed on wheat grain yield when spring season crops were followed by rice in a sequential cropping system. Significantly higher (p<0.001) rice equivalent yield (6.56 t ha-1) and net profit (Rs. 46489 ha-1) were obtained under mungbean-rice sequence. Similarly, significantly higher (p<0.001) wheat equivalent yield (8.74 t ha-1) and net profit (Rs. 44811 ha-1) were obtained under mungbean-rice-wheat sequence. Significantly higher yield of rice was obtained under 90 kg N ha-1 compared to control and had significant residual effect of N on wheat grain yield. Nitrogen topdressed at crown root initiation (CRI) and panicle initiation (PI) stages did not influence significantly on the grain yield of wheat. Therefore, for the long term sustainability of rice-wheat cropping system, inclusion of mungbean in the spring (fallow) season could be considered promising practice. Key words: Rice-wheat cropping system, sustainability, residue incorporation, nitrogen J. Inst. Agric. Anim. Sci. 27:53-58 (2006)